Saturnia jonasii Butler, 1877 on Jejudo Island, a new saturnid moth of South Korea with DNA data and morphology (Lepidoptera: Saturniidae) - Kim, Min Jee; Choi, Sei-Woong; Kim, Iksoo (Zootaxa, 2015)
Saturnia (Rinaca) jonasii Butler, 1877 is distributed in Japan, including Tsushima Island and Taiwan, whereas S. boisduvalii Eversmann, 1846 is distributed in northern areas, such as China, Russia, and South Korea. In the present study we found that the specimens from Mt. Hallasan on Jejudo, a southern remote offshore island, were S. jonasii, rather than S. boisduvalii based on morphology, DNA barcode, and nuclear elongation factor 1 alpha (EF-1α) sequences. The major morphological differences between the two species included the shape of wing pattern elements of fore- and hindwings and male and female genitalia. A DNA barcode analysis of the sequences of the Jejudo specimens and S. boisduvalii, along with those of Saturnia species obtained from a public database showed a minimum sequence divergence of 4.26% (28 bp). A phylogenetic analysis also showed clustering of the Jejudo specimens with S. jonasii, separating S. boisduvalii (Bayesian posterior probability = 0.99). The EF-1α-based sequence and phylogenetic analyses of the two species from Jejudo Island and the Korean mainland showed the uniqueness of the Jejudo specimens from S. boisduvalii collected on the Korean mainland, indicating distribution of S. jonasii on Jejudo Island in South Korea, instead of S. boisduvalii.